Hubungan Self Efficacy, Self Esteem dan Self Care dengan Kualitas Hidup Pasien Stroke di Ruang Rawat Inap Gedung B Rumah Sakit Otak dr.Drs. M. Hatta Bukittinggi Tahun 2022 - Glenn Andrew; Yuli Permata Sari; Marizki Putri (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Stroke is a condition in which clinical signs develop rapidly in the form of focal and global neurologic deficits, which can worsen and last for 24 hours. stroke can make a person's quality of life decrease because a stroke can make some body parts not function normally so that it can cause disruption of self-confidence, self-esteem and self-care of the sufferer. The purpose of this study was to determine the relationship between self-efficacy, self-esteem and self-care with the quality of life of stroke patients in the inpatient ward of building B, Rumah Sakit Otak. DR. Drs. M. Hatta Bukittinggi. This research is a non-experimental research that uses a correlational method with a cross sectional approach. The number of samples in this study were 64 people. The sampling technique in this study is non-probability sampling. Data collection using a questionnaire and data analysis using Chi-Square to determine the relationship of self-efficacy, self-esteem and self-care with the quality of life of stroke patients. The results showed that (57.8%) had a moderate level of self-efficacy, (76.6%) had a moderate level of self-esteem, (45.3%) had a highly dependent level of self-care and (35.9%) had a quality of life. currently. T Stroke is a condition in which clinical signs develop rapidly in the form of focal and global neurologic deficits, which can worsen and last for 24 hours. stroke can make a person's quality of life decrease because a stroke can make some body parts not function normally so that it can cause disruption of self-confidence, self-esteem and self-care of the sufferer. The purpose of this study was to determine the relationship between self-efficacy, self-esteem and self-care with the quality of life of stroke patients in the inpatient ward of building B, Rumah Sakit Otak. DR. Drs. M. Hatta Bukittinggi. This research is a non-experimental research that uses a correlational method with a cross sectional approach. The number of samples in this study were 64 people. The sampling technique in this study is non-probability sampling. Data collection using a questionnaire and data analysis using Chi-Square to determine the relationship of self-efficacy, self-esteem and self-care with the quality of life of stroke patients. The results showed that (57.8%) had a moderate level of self-efficacy, (76.6%) had a moderate level of self-esteem, (45.3%) had a highly dependent level of self-care and (35.9%) had a quality of life. currently. The results of this study also showed that there was a relationship between self-efficacy and self care with the quality of life of stroke patients with p value = 0.000, there was no relationship between self-esteem and quality of life of stroke patients with p value = 0.371. It can be concluded that there is a relationship between self-efficacy and self-care with the quality of life of stroke patients and there is no relationship of self-esteem with the quality of life of stroke patients in the inpatient ward of building B, Rumah Sakit Otak DR. Drs. M. Hatta Bukittinggi, for that it is expected to provide nursing education to stroke patients about self-efficacy, self-esteem and self-care.he results of this study also showed that there was a relationship between self-efficacy and self care with the quality of life of stroke patients with p value = 0.000, there was no relationship between self-esteem and quality of life of stroke patients with p value = 0.371. It can be concluded that there is a relationship between self-efficacy and self-care with the quality of life of stroke patients and there is no relationship of self-esteem with the quality of life of stroke patients in the inpatient ward of building B, Rumah Sakit Otak DR. Drs. M. Hatta Bukittinggi, for that it is expected to provide nursing education to stroke patients about self-efficacy, self-esteem and self-care.